Effects of Monsoon Activity on Monthly Phytoplankton Blooms in the Gulf of Thai Land in El Nino Year 2002 - Le, Van Thien (H. : ĐHQGHN, 2018)
The Gulf of Thailand is a semi-closed Gulf on the west and southwest side of the Indochina Penisula and experiences reversal monsoon. The object of the present study is to investigate monthly and spatial distributions of the phytoplankton in the Gulf of Thailand during whole El Nino year 2002 by using remote-sensing measurements of chlorophyll-a (Chl-a) and surface wind vectors. Results show that monthly and spatial variations of the phytoplankton blooms are primarily associated with the monsoonal winds. In general, the average monthly Chl-a concentrations were quite low (<0.5 mg m-3) most area of the Gulf, with a belt of higher Chl-a concentrations along the coast during throughout year. Phytoplankton blooms extensive ly offshore in the near-coastal area of the Gulf in January and February, which is consistent with the winter northeast monsoon. In particular, one peak of Chl-a concentrations was observed in December. Areas with higher Chl-a concentrations along the coast were observed in both winter and summer monsoon months.